Mekanisme Pasar Sekunder dan Produk Investasi Pasar Sekunder: Studi Kasus pada Efek Syariah - Anwar Anwar (Universitas 45 Surabaya, 2025)
As a source of finance for businesses in the form of firms and a way for the general public to invest, the capital market has become a crucial necessity in the modern economic period. The Indonesia Stock Exchange (IDX) is where shares are bought and sold on the secondary market. The buying/selling of shares and the transaction settlement process are the two primary steps in the secondary market securities trading system. This article seeks to identify secondary market investment products of Islamic securities case studies and to describe the technique of buying and selling transactions in the secondary market. The descriptive technique, a type of research methodology that was employed in this study.